Charge transfer to ground-state ions produces free electrons - You, Daehyun; Stumpf, Vasili; Gokhberg, Kirill; Kuleff, Alexander I.; Cederbaum, Lorenz S. (Nature Communications, 2017)
Inner-shell ionization of an isolated atom typically leads to Auger decay. In an environment, for example, a liquid or a van der Waals bonded system, this process will be modified, and becomes part of a complex cascade of relaxation steps. Understanding these steps is important, as they determine the production of slow electrons and singly charged radicals, the most abundant products in radiation chemistry. In this communication, we present experimental evidence for a so-far unobserved, but potentially very important step in such relaxation cascades: Multiply charged ionic states after Auger decay may partially be neutralized by electron transfer, simultaneously evoking the creation of a low-energy free electron (electron transfer-mediated decay). This process is effective even after Auger decay into the dicationic ground state. In our experiment, we observe the decay of Ne2+ produced after Ne 1s photoionization in Ne-Kr mixed clusters.